Depressive vulnerability, stressful life events and episode onset of major depression: a longitudinal model - Kendler, K. S. (Psychol Med, 2016)
BACKGROUND: The nature of the relationship between depressive vulnerability (DV) and acute adversity in the etiology of major depression (MD) remains poorly understood. METHOD: Stressful life events (SLEs) and MD onsets in the last year were assessed at four waves in cohort 1 (females) and at two waves in cohort 2 (males and females) from the Virginia Adult Twin Study. Structural equation modeling was conducted in Mplus. RESULTS: In cohort 1, DV was strongly indexed by depressive episodes over the four waves (paths from +0.72 to 0.79) and predicted by SLEs in the month of their occurrence (+0.31 to 0.36). Wave-specific DV was associated both with stable DV (+0.29 to 0.33) and by forward transmission of DV from the preceding wave (+0.33 to 0.36). SLEs were predicted by stable DV (+0.29) and from SLEs in the preceding month (+0.06). As the cohort aged, MD onsets were better indexed by DV and more poorly predicted by SLEs. Parameter estimates were similar in males and females from cohort 2. In individuals with prior depressive episodes, the association between MD onset and SLEs was weakened while the prediction of SLEs from DV was substantially strengthened. We found no evidence for ‘reverse causation’ from MD episodes to SLEs. CONCLUSION: The interrelationship between DV and acute adversity in the etiology of MD is complex and temporally dynamic. DV impacts on MD risk both directly and indirectly through selection into high stress environments. Over time, depressive episodes become more autonomous. Both DV and SLEs transmit forward over time and therefore form clear targets for intervention.